2016
DOI: 10.1002/jor.23238
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of a new broad‐spectrum antibiotic covalently bound to titanium surfaces

Abstract: Biofilm-associated infections, particularly those caused by Staphylococcus aureus, are a major cause of implant failure. Covalent coupling of broad-spectrum antimicrobials to implants is a promising approach to reduce the risk of infections. In this study, we developed titanium substrates on which the recently discovered antibacterial agent SPI031, a N-alkylated 3, 6-dihalogenocarbazol 1-(sec-butylamino)-3-(3,6-dichloro-9H-carbazol-9-yl)propan-2-ol, was covalently linked (SPI031-Ti). We found that SPI031-Ti su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 48 publications
0
32
1
Order By: Relevance
“…Moreover, additional tests demonstrated antibacterial activity against a representative selection of ESKAPE pathogens (see S5 Table ). Furthermore, we demonstrated that SPI031-functionalised titanium surfaces show significant antibacterial activity both in vitro and in vivo [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, additional tests demonstrated antibacterial activity against a representative selection of ESKAPE pathogens (see S5 Table ). Furthermore, we demonstrated that SPI031-functionalised titanium surfaces show significant antibacterial activity both in vitro and in vivo [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that the compound displays antifungal activity against Candida albicans [ 16 ]. Furthermore, we demonstrated that SPI031 has the clinical potential to be used as an antibacterial coating for implants, thereby reducing the incidence of implant-associated infections [ 17 ]. In the present study, we further investigated the antibacterial characteristics, including bactericidal activity and spontaneous resistance frequency, and mode of action of SPI031 using S .…”
Section: Introductionmentioning
confidence: 99%
“…The "grafting to" strategy permits an indirect grafting thanks to anchor molecules (silane [114][115][116][117], catechol [118][119][120][121], phosphate [122][123][124][125]). It enables titanium functionalization with various molecules in order to confer customized properties (Scheme 2).…”
Section: Grafting Tomentioning
confidence: 99%
“…Gerits et al [116] developed titanium substrates on which the recently discovered antibacterial agent SPI031, an N-alkylated 3, 6-dihalogenocarbazol 1-(sec-butylamino)-3-(3,6-dichloro-9H-carbazol-9yl)propan-2-ol, was covalently linked (SPI031-Ti) via a silane anchor (3-aminopropyl-triethoxy silane). They found that SPI031-Ti substrates prevent biofilm formation of S. aureus and P. aeruginosainvitro.…”
Section: Silane Anchormentioning
confidence: 99%
“…These facts have accentuated the pressing need to work towards developing new implants less susceptible to infections. Over the last decades, measures have been implemented to reduce the number of implant related infections by defining and putting into effect strict hygienic routines in the operating rooms and by using perioperative antibiotic prophylaxis [1][2][3][4][5][6][7][8][9]. Nevertheless, because the incidence of implant-related infections has continued to increase, the attention of scientists has focused on the development of newly biocompatible and antimicrobial materials that can be used as coatings for implantable medical devices [10,11].…”
Section: Introductionmentioning
confidence: 99%